Tinjauan Hukum Terhadap Kontrak Kerja Guru Honorer Ditinjau Dari Undang-Undang Nomor 14 Tahun 2005 Tentang Guru Dan Dosen Di SMAN 2 Kota Kupang - Dally, Azarya Syalom; Nubatonis, Orpa J; Jacob, Yossie M Y (Law Faculty, Nusa Cendana University, 2024)
This thesis examines the legal review of contracts for honorary teachers based on Law Number 14 of 2005 concerning Teachers and Lecturers. The study aims to identify and analyze the existence and legal implications of contracts entered into by honorary teachers, as well as their compliance with applicable regulations. The research employs a qualitative approach, utilizing document analysis and interviews with relevant parties, such as honorary teachers, school principals, and education law experts. The findings indicate that contracts for honorary teachers often do not meet the legal requirements established by the law, including basic rights, job protection, and employment status certainty. This study recommends the need for regulatory revisions and improved oversight of honorary teacher contracts to ensure fairness and the protection of their rights within the education system.